Cell-free DNA integrity and complement C4d as novel liquid biopsy biomarkers for paraneoplastic and non-paraneoplastic autoimmune encephalitis - Vakrakou, Aigli G.; Brinia, Maria-Evgenia; Cheiraki, Anastasia; Alexaki, Anastasia; Papadopoulou, Anna; Vatsellas, Giannis; Kokala Dimitropoulou, Vasileia; Derventzi, Anastasia; Constantinides, Vassilios C.; Stathopoulos, Panos; Boufidou, Foteini; Stefanis, Leonidas; et al. (Frontiers in Immunology, 2025)
BackgroundNeuronal injury in autoimmune encephalitis (AE) may involve antibodies or T cells, with or without complement activation. Cell-free DNA (cf-DNA), released during cell death, and the complement split product C4d may reflect underlying tissue damage and immune activation. This study examines cf-DNA and C4d levels in the CSF and plasma of AE patients, focusing on differences between paraneoplastic and non-paraneoplastic subtypes.MethodsThirty patients with AE (including paraneoplastic and non-paraneoplastic cases) and 18 healthy and disease controls were included. Total cf-DNA and cf-DNA integrity (cfDI), defined as the ALU-247/ALU-115 ratio, were measured in the CSF and plasma using quantitative polymerase chain reaction (qPCR). Interleukins IL-6 and IL-17A and the complement split product C4d were measured by ELISA. Clinical and radiological parameters were recorded.ResultsCSF cf-DNA levels were significantly elevated in AE patients compared to controls (p < 0.01). Patients with paraneoplastic AE showed higher cfDI values (p < 0.05), indicating a predominance of necrotic cell death. CSF C4d levels were markedly increased in AE patients, particularly those with tumors (p < 0.001). CSF C4d showed the highest diagnostic accuracy for detecting underlying tumors at AE diagnosis (AUC = 0.818). Elevated CSF ALU-115 levels (p = 0.025) were significantly associated with MRI-confirmed encephalitic lesions, while increased cfDI correlated with electroencephalogram abnormalities indicative of epileptiform activity, underscoring their potential as biomarkers of disease severity.ConclusionsElevated CSF levels of necrotic cf-DNA and the complement split product C4d reflect heightened CNS tissue injury and inflammatory activity in AE, particularly in paraneoplastic cases. These biomarkers may serve as useful tools for early diagnosis, disease monitoring, and subtype differentiation in AE.